Educational intervention using the Complementary Feeding Practice Module on maternal knowledge and behavior - Andriani, Rini; Supriyatno, Bambang; Kekalih, Aria; Gunardi, Hartono; Timan, Ina Susianti; Syafiq, Ahmad; Sidiartha, I Gusti Lanang; Sjarif, Damayanti Rusli (Paediatrica Indonesiana, 2025)
Background Correct complementary feeding practice can be a challenge for mothers. Our complementary feeding practice module provides practical information regarding evidence-based complementary feeding practices. Objective To assess the effect of educational intervention using the complementary feeding practice module on maternal knowledge and behavior and to compare the effect of video vs. printed delivery of the module. Methods This open label randomized controlled trial included mothers with babies aged 4 to 8 months in Pontianak, West Kalimantan, Indonesia, who engaged in complementary feeding. Subjects were randomized into an intervention group that received a printed booklet of the module, an intervention group that received a video of the module, or a control group that received the standard Indonesian mother and child health (MCH) handbook. Maternal knowledge and behavior regarding complementary feeding practice were assessed before and after the educational intervention using the PI-MPASI questionnaire. Results Of 360 mothers screened, 241 subjects were randomized into the video education group (n=76), the printed education group (n=84), and the control group (n=81). A total of 212 subjects completed the study by submitting both the pre- and post-test: 66 in the video group, 74 in the printed booklet group, and 72 in the control group. Subjects who received the module (video or printed) had significantly higher knowledge and behavior scores than those in the control group. Video education was associated with a greater increase in behavior score than printed education and control. The outcome of video education was not influenced by maternal educational level. Conclusion  Education using a simple and practical video or printed module improves maternal knowledge and behavior in complementary feeding practices. Video education is associated with a greater improvement in maternal complementary feeding behavior than printed education.